2015
DOI: 10.1109/tevc.2014.2362729
|View full text |Cite
|
Sign up to set email alerts
|

Solving Uncompromising Problems With Lexicase Selection

Abstract: Abstract-We describe a broad class of problems, called "uncompromising problems," characterized by the requirement that solutions must perform optimally on each of many test cases. Many of the problems that have long motivated genetic programming research, including the automation of many traditional programming tasks, are uncompromising. We describe and analyze the recently proposed "lexicase" parent selection algorition and show that it can facilitate the solution of uncompromising problems by genetic progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 23 publications
2
73
0
Order By: Relevance
“…docfk employs f (k) to evaluate clustering result and choose the optimal k for the given data. Apart from these variants of doc, we run the conventional Koza-style GP (gp in the following), which employs tournament of size 7 in the selection phase, implicit fitness sharing (ifs, Section 3.1) also with tournament of size 7, lexicase selection (lex) [4] (Section 3.3) and doclex, the hybrid of doc and lex proposed in Section 3.4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…docfk employs f (k) to evaluate clustering result and choose the optimal k for the given data. Apart from these variants of doc, we run the conventional Koza-style GP (gp in the following), which employs tournament of size 7 in the selection phase, implicit fitness sharing (ifs, Section 3.1) also with tournament of size 7, lexicase selection (lex) [4] (Section 3.3) and doclex, the hybrid of doc and lex proposed in Section 3.4.…”
Section: Methodsmentioning
confidence: 99%
“…Recent experiments by Helmuth et al [4] demonstrate LEX's strengths in problem solving and diversity maintenance.…”
Section: Lexicase Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties of tests are calculated from the current population and 346 K. Krawiec, P. Liskowski thus change with evolution, which can help escaping local minima and diversifies the population. Diversification maintenance was also the main motivation for the recent Lexicase selection algorithm [11], that avoids aggregating interaction outcomes altogether: in each selection act, a random permutation of tests is generated, and the program from the current population which passes the longest uninterrupted sequence of tests is selected. Lexicase proved very effective in a range of contexts and applications.…”
Section: Related Workmentioning
confidence: 99%
“…Further details of the Lexicase algorithm are presented in the next section. Helmuth et al (2014) have shown that Lexicase is effective at solving challenging problems in GP. Although it was initially introduced for GP, Lexicase has the potential to be a very effective algorithm in evolutionary robotics where objectives relating to performance (e.g.…”
Section: Introductionmentioning
confidence: 99%